Working from home, commuting, and gender - Nagler, Markus; Rincke, Johannes; Winkler, Erwin (Journal of Population Economics, 2024)
Work from home (WFH) arrangements may provide an opportunity to reduce gender gaps in labor market outcomes by reducing the gender differences in the willingness to commute. Using a stated-preference experiment among German employees, we estimate workers’ valuation of working from home and its impact on willingness-to-pay to avoid commuting by gender after the end of the COVID pandemic. We show that workers are willing to give up 7.7% of their earnings for full WFH and 5.4% for 2-day WFH on average. The willingness-to-pay for WFH steeply increases with commuting distance, in line with WFH reducing the need for long commutes for many workers. Importantly, we find that WFH reduces, but does not close, the gender gap in willingness-to-pay to avoid commuting. This result is unaffected by accounting for underage children in the household. This suggests that hopes of technology closing the gender wage gap are premature.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Commuting; Gender; Working conditions; Working from home